1992
DOI: 10.2307/1131344
|View full text |Cite
|
Sign up to set email alerts
|

A Family Process Model of Economic Hardship and Adjustment of Early Adolescent Boys

Abstract: We propose a family process model that links economic stress in family life to prosocial and problematic adolescent adjustment. Employing a sample of 205 seventh-grade boys aged 12 to 14 years (M = 12.7) and living in intact families in the rural Midwest, the theoretical constructs in the model were measured using both trained observer and family member reports. In general, results were consistent with the proposed model. Objective economic conditions such as per capita income and unstable work were related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

120
1,090
15
29

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,293 publications
(1,265 citation statements)
references
References 8 publications
120
1,090
15
29
Order By: Relevance
“…Children's subsequent drift into nonconventional peer associations serves to further reinforce coercive interaction styles. Conger et al, (1992) replicated Patterson's findings with adolescent boys and extended the model for adolescent girls (Conger et al, 1993). Mason, Cauce, Gonzales, Hiraga, Grove (1998) have tested aspects of this model with African American families with essentially the same results.…”
Section: Theoretical Backgroundsupporting
confidence: 52%
“…Children's subsequent drift into nonconventional peer associations serves to further reinforce coercive interaction styles. Conger et al, (1992) replicated Patterson's findings with adolescent boys and extended the model for adolescent girls (Conger et al, 1993). Mason, Cauce, Gonzales, Hiraga, Grove (1998) have tested aspects of this model with African American families with essentially the same results.…”
Section: Theoretical Backgroundsupporting
confidence: 52%
“…High levels of hostility have been associated with child externalizing behaviors in a number of studies (e.g., Conger, Conger, Elder, Lorenz, Simons, & Whitbeck, 1992;Conger, Conger, Elder, Lorenz, Simons, & Whitbeck, 1993;Conger, Ge, Elder, Lorenz, & Simons, 1994;O'Leary, Slep, & Reid, 1999;Patterson, Reid, & Dishion, 1992). For example, Patterson (1982) and colleagues (e.g., Patterson, Reid, & Dishion, 1992;Snyder & Patterson, 1995) have studied extensively the coercive processes that operate through hostility and lead to externalizing problems.…”
Section: Individual Parenting Behaviorsmentioning
confidence: 99%
“…Finally, we considered only those studies examining children in the age range of two to eighteen, as our child outcomes of interest (externalizing and internalizing problems) cannot be appropriately diagnosed or reliably assessed in children younger than two, and we defined children as individuals younger than 18 years of age. From the original 121 studies identified, 17 met the above-described inclusion criteria (i.e., Brody, Kim, Murray, & Brown, 2004;Chi & Hinshaw, 2002;Conger, Patterson, & Ge, 1995;Conger et al, 1992;Conger et al, 1993;DeGarmo, Patterson, & Forgatch, 2004;Dumas & Serketich, 1994;Fendrich, Warner, & Weissman, 1990;Frye & Garber, 2005;Hammen et al, 2004;Herwig, Wirtz, & Bengel, 2004;Jaser et al, 2005;Kim & Brody, 2005;Low & Stocker, 2005;Marchand & Hock, 1998;Nelson, Hammen, Brennan, & Ullman, 2003;Panaccione & Wahler, 1986).…”
Section: Criteria For Inclusionmentioning
confidence: 99%
“…The capability to implement known best practice is often disrupted by parental stressors such as separation or divorce, job loss [19], increased work hours [8], or even by a generalized growing disaffection (depression) and longterm disadvantage [20]. Culture and the media convey consistent negative images of parentteen relationships that undermine parent morale and self-efficacy [10].…”
Section: Introductionmentioning
confidence: 99%